A Cross-Sectional Study of Predictive Factors of Self-Management Among Adolescents with Type 1 Diabetes. - Kajonwiboolpol, Supachai; Patoomwan, Autchareeya; Punyoo, Jiraporn (Pacific Rim International Journal of Nursing Research)
Uncontrolled blood glucose in adolescents with type 1 diabetes leads to many complications that are life-threatening and affect their quality of life. Self-management is an approach that allows adolescents to achieve good glycemic control. Therefore, this predictive correlation study aimed to investigate self-management among adolescents with type 1 diabetes and to examine the predictive power of age, parenting styles, and patient-provider relationship satisfaction on self-management. Purposive sampling was employed to recruit 93 adolescents aged 10 to 19 years with type 1 diabetes who were receiving follow-up care at two tertiary hospitals in Bangkok, Thailand. The research instruments used were the Self-Management Behavior of Adolescents with T1DM, the Parenting Style, and the Thai version of the Medical Interview Satisfaction Scale (MISS-21). Descriptive statistics and multiple regression were employed to analyze the data. The results found that the mean score of self-management behaviors was high. All variables, including age, authoritative, authoritarian, permissive, and uninvolved parenting styles, as well as patient-provider relationship satisfaction, explained 49.4% of the variance in self-management behaviors. However, only authoritative parenting style, uninvolved parenting style, and patient-provider relationship satisfaction were statistically significant predictors of self-management, with patient-provider relationship satisfaction being the strongest. Nurses can use this finding to design and test an intervention program that emphasizes encouraging authoritative parenting while discouraging uninvolved parenting and promoting the patient-provider relationship in the management of diabetes. Future studies should investigate the cultural variations of parenting styles, self-management, and glycemic control in adolescents from more diverse cultural and ethnic backgrounds.